Politeness as the Effort to Maintain Social Relation in the Novel Emma by Jane Austen - Qori Annisa; Jepri (Faculty of Letters Universitas Balikpapan, 2023)
This thesis explores politeness as the effort to maintain social relations in the novel Emma by Jane Austen. There are two objectives of this research; 1) to find out about the forms of politeness in the novel Emma by Jane Austen and 2) to find out how politeness maintains the social relations in the novel Emma by Jane Austen. The theory used in this research is the politeness theory by Brown and Levinson and social relation by Max Weber. The methodology employed is qualitative research in which the researcher tries to present the material descriptively. As for the source of data, these were collected from quotations in the novel to find the character's utterances which show the appropriate manner in particular situations to achieve and maintain successful social relationship with the addressee. The result of this research based on the findings concluded that negative politeness 35% is dominating in maintaining communal 20% and associative 15% relationships. Followed by positive politeness 28% is also widely used in the novel to maintain communal 15% and associative relationships 12%. Both appear in characters' utterances to indicate someone with respect and where only a part of the occasion or means of conflict is eliminated.